The Effects of School and Neighborhood Characteristics On Delinquency, Drug and Alcohol Issues, Early Childbearing, and Welfare Receipt - Otto, Bobette (2014)
Little research has examined the impact of school and neighborhood racial composition on delinquency, arrest, incarceration, drug issues, early childbearing, and welfare collection. The purpose of this study is to explore these particular relationships. For this project, I use Add Health data. Based on past literature and theories concerning the consequences of racially segregated schools and neighborhoods, I hypothesized that students who attended/lived in schools/neighborhoods with a higher concentration of racial minorities would be more likely to participate in delinquent acts, get arrested, be incarcerated, have issues with drugs and alcohol, have a teenage pregnancy (or their partner did), and collect welfare during young adulthood. Although research on these outcomes is sparse, Lafree an Arum (2006) and Johnson (2011) found that increased minority racial composition in schools was related to delinquency and incarceration, while those studying neighborhoods have found similar results (Massey and Denton 1993; Krivo and Peterson 1996). Further, other research has shown that alcohol and tobacco companies target minority neighborhoods (Rabow and Watt 1982; Moore, Williams, and Qualls 1996) and this exposure could lead to higher rates of alcohol and tobacco use. The theoretical frameworks I used initially to frame how school minority concentration affects disadvantage were not completely supported. When school and neighborhood racial composition was significant, it was in a direction not predicted, which is an interesting finding that needs further examination. Overall, family structure, racial background, and prior background were significant and consistent predictors. I argue that family background and systematic racism are fundamental in explaining racial inequality